Sensing injustice?: defences to murder - Howe, Adrian (Feminist responses to injustices of the state and its institutions, 2024)
On any feminist reading, men ‘getting away’ with murdering their women partners and former partners is self-evidently unjust. But could it be that when feminists demand justice for femicide victims they fall into a binary trap of assuming justice to be the self-evident opposite of injustice? This chapter explores that question in relation to feminist advocacy of criminal law reforms curtailing victim-blaming defences to murder that reinscribe historically mandated excuses for killing women and which have, until recently, frequently resulted in manslaughter verdicts that diminish victims by holding them account for contributing to their own deaths. In short, the reforms, now implemented across several Anglophone jurisdictions, were designed to counter a perceived injustice in the criminal justice system’s handling of intimate partner femicide cases. Have they had its intended effect of stopping men getting away with murder, thereby delivering justice to victims?